TINGKAT KEPATUHAN DIET DENGAN DERAJAT HIPERTENSI PADA LANSIA - Ade Reffi Sapitri; Lia Meilianingsih; Supriadi Supriadi; Achmad Husni (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2025)
This research was motivated by the results of Riskesdas data which stated that the prevalence of hypertension in West Java had increased (39.6%) and the city of Bandung was in fourth position (696,372 people). Garuda Health Center is one of the top five (19,111 cases) with the highest prevalence of hypertension in the city of Bandung. This study aims to determine the level of dietary adherence, determine the degree of hypertension, and the relationship between the level of dietary compliance and the degree of hypertension in elderly hypertensives. The research design uses analytics with a cross-sectional approach. The number of samples from a population of 10.82% of Indonesian elderly was found to be 37 elderly people. The instruments used were a compliance-level questionnaire and a sphygmomanometer to measure blood pressure. Univariate analysis used the frequency distribution, and bivariate analysis used the chi-square test. The results showed that more than half (62.2%) of the respondents were non-compliant, more than half (67.6%) of the respondents were classified as having grade 2 hypertension, and there was a relationship between the level of dietary compliance and the degree of hypertension in the elderly with hypertension with a P value (0.000) < α (0.05). Researchers recommend that prolanis program holders hold demonstrations during prolongs activities about what foods can be consumed. The elderly can comply with the hypertension diet by maintaining their diet, reducing salt consumption, and consuming lots of fruits and vegetables. Future researchers can conduct research on other factors that influence the degree of hypertension.